Reduced plantar sole sensitivity facilitates early adaptation to a visual rotation pointing task when standing upright - Billot,M.; Teasdale, N.; Gagne Lemieux, L.; Germain Robitaille, M.; Simoneau, M. (Journal of Human Kinetics, 2016)
Humans are capable of pointing to a target with accuracy. However, when vision is distorted through a visual rotation or mirror-reversed vision, the performance is initially degraded and thereafter improves with practice. There are suggestions this gradual improvement results from a sensorimotor recalibration involving initial gating of the somatosensory information from the pointing hand. In the present experiment, we examined if this process interfered with balance control by asking participants to point to targets with a visual rotation from a standing posture. This duality in processing sensory information (i.e., gating sensory signals from the hand while processing those arising from the control of balance) could generate initial interference leading to a degraded pointing performance. We hypothesized that if this is the case, the attenuation of plantar sole somatosensory information through cooling could reduce the sensorimotor interference, and facilitate the early adaptation (i.e. improvement in the pointing task). Results supported this hypothesis. These observations suggest that processing sensory information for balance control interferes with the sensorimotor recalibration process imposed by a pointing task when vision is rotated.